Students, professors and preceptors’ perspectives of physical therapy undergraduate and graduate courses in emergency remote teaching during social distancing: a cross-sectional study - electronic survey - Gislene Gomes da Silva; Alessandra Narciso Garcia; Diego Galace de Freitas (Fisioterapia e Pesquisa)
ABSTRACT During the period of emergency remote teaching (ERT), it became crucial to understand the perceptions of those involved in the national pedagogical scenario. This study aimed to describe the perspectives of students, professors, and physical therapy preceptors on ERT during social distancing due to COVID-19. The survey was distributed through social media and registered 995 visitors, resulting in 709 valid responses. The sample included 59 professors and preceptors as well as 650 undergraduate and graduate students. Most participants were female (80.2%), students were aged from 20 to 34 years and professors and preceptor from 20 to 49 years; the latter were predominantly linked to private higher education institutions (92%), mostly in the Brazilian Southeast (82.9%). Confidence in digital platforms use varied between groups: 81.4% of professors and preceptors reported high levels of confidence, while only 58.3% of students reported the same. The results highlighted the financial impact (86.6%), the difficulties in accessing classes (76.6%) and the preference for the continued use of digital platforms (79.5%). Engagement and interaction during classes were affected (83.2%), as well as academic and professional performance (79.4%), especially among professors and preceptors (79.5%). The correlation between confidence in digital platforms use and academic/professional performance was significant for teachers and preceptors (r=0.323) and not significant for students and the overall sample. Confidence in technology use proved to be vital to the success of ERT. Despite the negative effects observed in the variables analyzed, the preference for remote learning was high.